N-Acetylcysteine for non-paracetamol drug-induced liver injury: A systemic review - Chughlay, Mohamed Farouk (Division of Clinical Pharmacology, 2016)
Aims: There are limited therapeutic options for drug-induced liver injury (DILI). N-acetylcysteine (NAC ) is known to be of benefit in management of DILI due to paracetamol overdose and may also be useful in the management of non-paracetamol DILI. Our objective was to systematically review evidence for the use of NAC as a therapeutic option for non-paracetamol DILI. Methods: We conducted a systematic review of the benefit and harm of NAC in non-paracetamol DILI. We searched for randomized controlled trials (RCTs) and prospective cohort studies. We searched several bibliographic databases (including PubMed, Scopus, CINAHL, CENTRAL), grey literature sources, conference proceedings and ongoing trials. Our pre-specified primary outcomes were all cause and DILI related mortality, time to normalisation of liver biochemistry and adverse events. Secondary outcomes were proportion receiving liver transplant, time to transplantation, transplant-free survival and hospitalization duration. Two reviewers independently assessed studies for inclusion and quality and extracted data. Results: We identified one RCT of NAC versus placebo in patients with non-paracetamol acute liver failure. There was no difference in the primary outcomes of overall survival at 3-weeks between NAC [70%, 95% Confidence Interval (CI)= 60% to 81%, n=81 ] and placebo (66%, 95% C I= 56% to 77%, n=92 ). NAC significantly improved the secondary outcomes of transplant-free survival compared with placebo : 40% NAC ( 95% CI= 28% to 51%) versus 27% placebo ( 95% CI= 18% to 37%). A subgroup analysis according to aetiology found improved transplant-free survival in patients with non-paracetamol DILI; NAC (58%, n=19 ) versus placebo (27%, n=26 ); odds ratio (OR) 0.27 (95% CI= 0.076 to 0.942 ). O verall survival was similar NAC ( 79% ) v ersus placebo ( 65% ); OR 0.5 0 ( 95% CI= 0.13 to 1.98 ). Conclusion : Current available evidence is limited and does not allow for any firm conclusions to be made regarding the role of NAC in non-paracetamol DILI. We therefore highlight the need for further research in this area.